2001
DOI: 10.1097/00000539-200107000-00030
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Uterine and Umbilical Blood Flows on the Transfer of Propofol Across the Human Placenta During In Vitro Perfusion

Abstract: Uterine and umbilical blood flows are determinant features in controlling the placental transfer of propofol, and, therefore, changes in these variables would significantly affect the extent of fetal exposure to propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Conversely, increased umbilical blood flow facilitated the placental transfer of propofol in vitro. 26 The drugs in this study are known to alter blood flow: medetomidine will decrease blood flow to a range of organs 18 while ketamine has little effect on uterine blood flow. 27,28 The interaction of these effects in this study is unknown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, increased umbilical blood flow facilitated the placental transfer of propofol in vitro. 26 The drugs in this study are known to alter blood flow: medetomidine will decrease blood flow to a range of organs 18 while ketamine has little effect on uterine blood flow. 27,28 The interaction of these effects in this study is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Uterine and umbilical blood flow will also influence the transfer of drugs across the placental barrier. 26 Increased uterine blood flow is likely to decrease the extraction of drugs by the placenta, and maintain maternal plasma concentrations at a higher level for a longer period of time. Conversely, increased umbilical blood flow facilitated the placental transfer of propofol in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Flow rates of 3 and 12 ml/min are maintained in the fetal and maternal circulations, respectively. Flow rates used in the perfusion model vary between laboratories 14 and can influence the time to achieve transplacental transfer and steady state between the fetal and maternal circulations 16 , 17 …”
Section: Description Of the Experimental Modelmentioning
confidence: 99%
“…Propofol pharmacokinetic (PK) properties are well established in pediatric and adult populations, but little is known of propofol disposition in the unborn fetus especially during open fetal surgery. Many in vitro studies using human dually perfused cotyledon demonstrated that propofol is highly lipophilic and rapidly diffuses across the placenta [ 4 , 5 ]; however, the extent of fetal drug exposure during maternal propofol administration is largely unknown. In the third trimester, the fetal exposure of propofol in utero has been studied in parturients undergoing cesarean section.…”
Section: Introductionmentioning
confidence: 99%